PENGARUH BRAND IMAGE TERHADAP LOYALITAS KONSUMEN KRIM PEMUTIH WAJAH POND’S DI HIPERMARKET GIANT MALL OLYMPIC GARDEN MALANG - Irene Yolanda (Universitas Katolik Widya Karya Malang, 2019)
Consumer loyalty in the business world is very important. Consumer loyalty makes it easier for companies to forecast demand and create barriers for other companies to enter and dominate the market. The research takes the brand image as the independent variable that sought the significance of its influence on consumer loyalty POND'S whitening cream, which also aims to find out which factor is the most dominant brand image formers that influence consumer loyalty POND'S face bleaching cream.Methods of data collection using questionnaires containing statements distributed to 80 people using Purposive Sampling technique.Qualitative descriptive analysis resulted from statistical data processing with SPSS 16.0 software, by performing instrument test, classical assumption test, multiple linear regression, and effective donation test. The result of research indicates that the factors of forming of brand image have significant influence simultaneously to consumer loyalty of POND'S face bleaching cream with risk factor as the most dominant influence factor. Kata Kunci: brand image, consumer loyalty